The Effectiveness of Meanin-Centered Therapy on the Dimensions of Quality of Life in Women with Grief Syndrome Following Cancer-Related Amputation - Dardashtinia , Nika; Jahandar, Baharak; Abasian Najafabadi , Athar; Talebi, Gholamreza (Psychology of Woman Journal, 2026)
Objective: The aim of this study was to investigate the effectiveness of Meanin-Centered Therapy on the dimensions of quality of life in women experiencing grief syndrome following cancer-related amputation. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group and a follow-up phase. The statistical population consisted of women with breast cancer experiencing death anxiety and grief symptoms following amputation, who were recruited from specialized oncology centers in Isfahan. A total of 36 participants were selected using purposive sampling and randomly assigned to an experimental group (n = 18) and a control group (n = 18). The experimental group received an eight-session group-based Meanin-Centered Therapy intervention, while the control group did not receive any psychological intervention during the study period. Data were collected using the WHOQOL-BREF, the Grief Experience Questionnaire, and the Death Anxiety Scale. Data analysis was conducted using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-27, with a significance level set at p < 0.05. Findings: The results indicated significant effects of time, group, and the interaction between time and group on all dimensions of quality of life (p < 0.001). Participants in the experimental group showed significant improvements in physical health, psychological health, social relationships, and environmental health at posttest compared to pretest, while no significant changes were observed in the control group. Bonferroni post-hoc analyses revealed that the differences between pretest and posttest, as well as between pretest and follow-up, were statistically significant (p < 0.001), whereas no significant differences were found between posttest and follow-up (p > 0.05), indicating stability of the intervention effects over time. Effect size indices demonstrated large practical significance across all variables. Conclusion: Meanin-Centered Therapy is an effective intervention for improving multiple dimensions of quality of life in women experiencing grief syndrome following cancer-related amputation, and its effects are sustained over time, suggesting its utility as a meaning-centered therapeutic approach in psychosocial oncology care.